Development of Technology of Suspension Polymerization of Propylene at "Tomskneftekhim" Company - Mayer E. A. Eduard Aleksandrovich; Pestryakov A. N. Aleksey Nikolaevich; Klimov I. G.; Dudchenko V. K. (2012, 2012)
Title screen